Predicting Quarter-Life Crisis in Emerging Adulthood through Self-Efficacy and Resilience - Ramadani, Noer Aisyah; Mubina, Nuram; Minarsih, Yulyanti (Philanthropy: Journal of Psychology, 2025)
Emerging adulthood is a transitional stage toward adulthood that often brings about feelings of anxiety and despair, which are characteristic of a quarter-life crisis. This study aims to examine the influence of self-efficacy and resilience on quarter-life crisis among individuals in the emerging adulthood stage in Karawang. This research employed a quantitative approach using multiple linear regression analysis, conducted with SPSS version 25.0. The sample consisted of 352 respondents aged between 20 and 25 years. The instruments used were the General Self-Efficacy Scale 12-Item (GSES-12) and the 10-Item Connor-Davidson Resilience Scale (CD-RISC-10), which were adopted scales, as well as the Quarter Life Crisis Scale, which was adapted for this study. The results of the hypothesis testing indicated a simultaneous effect of self-efficacy and resilience on quarter-life crisis, with a significance value of 0.000 (p < 0.05) and a total contribution of 26%. Partially, self-efficacy contributed 23.89%, while resilience contributed 2.52%, and both variables showed a positive relationship with quarter-life crisis. These findings highlight the importance for individuals in emerging adulthood to develop realistic expectations and the ability to manage negative emotions, anxiety, and worries that may arise during the quarter-life crisis phase.